Estudo da variabilidade genética na miopatia central core: aperfeiçoando o screening de mutações no gene RYR1 - Cuperman, Thais [UNIFESP] (2014)
Introduction: Central core disease (CCD) is characterized by the presence of central core-like areas in muscle fibers. Patients with RYR-related CCD usually have mild or moderate axial and proximal weakness, hypotonia and motor developmental delay. CCD is associated with susceptibility to malignant hyperthermia (MH), and both conditions have been linked to mutations in human RYR1 gene, which encodes a calcium release channel known as ryanodine receptor (RyR1). RYR1 mutational spectrum linked with CCD includes more than 200 described mutations mostly heterozygous dominant missense mutations and minor deletions or duplications. Definite diagnosis of CCD is done by clinical history and evaluation, histopathological analyses of muscle biopsy and, recently, genetic testing of gene?s ?hot spots?, because RYR1 is a large gene and direct sequencing of each exon is laborious. Here, we tested Multiplex Ligation-dependent Probe Amplification (MLPA) as an alternative and simple method for screening patients with histological diagnosis or family history of CCD Objective: To test MLPA technique for screening patients with histological diagnosis or family history of CCD and its precision to detect possible mutations in RYR1 gene, comparing to direct sequencing results of the same exons. Methods: We used DNA database specimens of patients with histological diagnosis or family for MLPA and direct sequencing testing. Results: From 35 patients diagnosed with CCD in three different institutions, 24 (68,6%) had mutations found in direct sequencing and twelve (34,3%) in MLPA. Mutations in exon 101 (c.14582 G>A and c.14581 C>T) were the most prevalent in sequencing and MLPA. The missense mutation c.14256 A>C in exon 98 was the most prevalent polymorphism identified. A new mutation in exon 100 (c.14411 A>C) was detected by direct sequencing. Conclusion: MLPA had shown to be a simple but relevant tool to help diagnosing CCD; moreover, it is especially useful in diagnosing family members of patients with known mutations detectable by MLPA considering the difficulty to detect the mutations in RYR1 gene.